The roles of rainfall, soil properties, and species traits in flowering phenology along a savanna-seasonally dry tropical forest gradient - Neves, Sâmia Paula Santos; de Miranda, Lia d´Afonsêca Pedreira; Rossatto, Davi Rodrigo [UNESP]; Funch, Ligia Silveira (Springer Nature, 2017)
We investigated flowering phenology in a semiarid macroclimate along an environmental gradient encompassing neotropical savanna, transition, and seasonally dry tropical forest (SDTF) areas in the Chapada Diamantina Mountains, northeastern Brazil. We expected to find divergence in flowering patterns between the plant communities studied that would be explained by distinct functional traits selected by differences in rainfall volumes and soil properties. Bud and flower productions were monitored in 809 individuals between January 2010 and March 2012. The savanna exhibited a continuous flowering pattern, while the transition and SDTF areas showed seasonal flowering associated with rainfall. Environmental variables and plant traits (wood densities, water potentials, and water storage capacities) were related to the observed flowering strategies of woody species. The high diversity of functional groups in the savanna was determined by higher plant water potentials that were related to low wood densities and the availability of soil water. The role of rainfall, especially the rainfall volumes during the dry season, is critical in defining different flowering patterns at the community level. The physical properties of the soil selected the presence of species with distinct water-use strategies (low wood density species in savanna areas, and high wood density species in the transition zone and forest), which in turn affected their flowering.
Keywords: Functional groups; Heterogeneity; Seasonality; Water potentials; Wood density